1997
DOI: 10.1007/bf02445108
|View full text |Cite
|
Sign up to set email alerts
|

Plasma DNA levels in patients with atherosclerotic involvement of the major arteries of the head and lateral amyotrophic sclerosis

Abstract: Measurements of DNA concentrations by fluorescence of the DNA--bisBenzimide complex in the plasma of normal subjects, patients with disorders of cerebral circulation of different severity caused by atherosclerotic involvement of the carotid and/or spinal arteries (after the acute stage of brain stroke), and patients with lateral amyotrophic sclerosis showed a significant increase in its content vs. the norm. Electrophoresis of DNA isolated from plasma showed that in the patients it is represented not only by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…86 The concentration of DNA detected by Hoechst 33258, a fluorescent DNA dye, was increased in plasma of patients with coronary artery atherosclerosis compared with healthy controls. 87 In accord with this finding, an independent study identified increased levels of nucleosomes in plasma from 231 atherosclerosis patients. 88 Plasma nucleosomes positively correlated with plasma concentration of markers of endothelium and coagulation activation (e.g., thrombin-antithrombin complexes and von Willebrand factor).…”
Section: Atherosclerosismentioning
confidence: 72%
“…86 The concentration of DNA detected by Hoechst 33258, a fluorescent DNA dye, was increased in plasma of patients with coronary artery atherosclerosis compared with healthy controls. 87 In accord with this finding, an independent study identified increased levels of nucleosomes in plasma from 231 atherosclerosis patients. 88 Plasma nucleosomes positively correlated with plasma concentration of markers of endothelium and coagulation activation (e.g., thrombin-antithrombin complexes and von Willebrand factor).…”
Section: Atherosclerosismentioning
confidence: 72%
“…In clinical trials, it was shown that the hemodynamic resistance in apparently healthy donors inversely correlated with the concentration of pDNA, while in patients with ischemic stroke the hemodynamic resistance significantly increased and inversely correlated with the amount of the circulating long pDNA fragments (>20 kb). [4][5][6][7] During the first 24 h after ischemic stroke there is a 7-to 20-fold elevation in the concentration of pDNA, [8][9][10] resulting from the appearance of a great number (up to 80%) of short fragments (<1-0.2 kb), with a simultaneous decrease in the number of long ones (>23 kb). Oligonucleosomes were found in 100% of patients who had a severe stroke and a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%